Transient Receptor Potential Cation Channel Subfamily V Member 4 Mediates Pyroptosis in Chronic Obstructive Pulmonary Disease - Rao, Yafei; Gai, Xiaoyan; Xiong, Jing; Le, Yanqing; Sun, Yongchang (Frontiers in Physiology, 2021)
TRPV4, a calcium permeable cation selective channel, was found to be involved in chronic obstructive pulmonary disease (COPD) through releasing ATP and IL-1β. Pyroptosis, a newly discovered pro-inflammatory cell death, was induced by cigarette smoke (CS) in airway epithelial cells (AECs). More recent studies indicated that blocking Ca2+ influx effectively inhibited pyroptosis. Therefore, we asked whether TRPV4 mediated CS-induced pyroptosis of AECs and hence participated in the pathogenesis of COPD. We found that pyroptosis and TRPV4 were upregulated in AECs from patients with COPD and long-term CS-exposed mice. Moreover, pharmacological inhibition or knockdown of TRPV4 function alleviated CS extract (CSE)-induced pyroptosis by inhibiting NACHT, LRP, PYD domains-containing protein 3 (NLRP3) inflammasome/activated caspase-1/gasdermin D pathway, decreasing the number of PI positive cells and lactate dehydrogenase (LDH) release, decreasing the expression of pro- inflammatory interleukin gene (IL)-1β, IL-8, and IL-18 expression, as well as increasing anti-inflammatory gene expression [NAD(P)H quinone dehydrogenase 1 (NQO1), superoxide dismutase 2 (mitochondrial) (MNSOD), and catalase, (CAT)]. Moreover, pharmacological inhibition or knockdown of TRPV4 function significantly relieved CSE-induced mitochondrial damage including decreased mitochondrial membrane potential, mitochondrial fusion protein (OPA1, MFN2) expression, and increased mitochondrial fission protein (DRP1, MFF) expression. Taken together, these findings indicate that TRPV4 mediates AEC pyroptosis via NLRP3/caspase-1/GSDMD pathway in COPD.